Ferulic Acid and Eugenol Have Different Abilities to Maintain Their Inhibitory Activity Against Listeria monocytogenes in Emulsified Systems - Pernin, Aurélia; Bosc, Véronique; Maillard, Marie-Noëlle; Dubois-Brissonnet, Florence (Frontiers in Microbiology, 2019)
Natural phenolic compounds are found in large quantities in plants and plant extracts and byproducts from agro-industries. They could be used to ensure food quality and safety due to their antimicrobial properties demonstrated in systems such as culture medium. The aim of this study was to evaluate the ability of two natural phenolic compounds, ferulic acid and eugenol, to maintain their inhibitory activity against the growth of Listeria monocytogenes in an oil-in-water emulsion, simulating a complex food system. The minimum inhibitory concentration (MIC) of each phenolic compound was first determined in culture medium, consisting of TS broth and an added emulsifier. Whey proteins and Tween 80 increased the MIC of the antimicrobial activity of eugenol. The MIC of ferulic acid was less affected by the addition of Tween 80. The inhibitory activities of both phenolic compounds were then compared at the same concentration in emulsions and their corresponding aqueous phases by following the growth of L. monocytogenes by plate counting. In emulsified systems, eugenol lost the high inhibitory activity observed in the aqueous phase, whereas ferulic acid retained it. The partition coefficient (logPoct/wat) appears to be a key factor. Eugenol (logPoct/wat = 2.61) dispersed in the aqueous phase intercalates into the bacterial membrane and has high antimicrobial activity. In contrast, it likely preferentially partitions into the lipid droplets when dispersed in an emulsion, consequently losing its antimicrobial activity. As ferulic acid is more hydrophilic, a higher proportion probably remains in the aqueous phase of the emulsion, retaining its antimicrobial activity.